The Relevance of Conventional Management Accounting Techniques - Dahal, Rewan Kumar (Nepal Journal of Multidisciplinary Research, 2021)
The study's objective was to observe the relevance of conventional management accounting techniques (CMATs) in Nepalese manufacturing companies (NMCs). A structured survey questionnaire was utilized to collect data. The population of the study included all the manufacturing companies that were functioning in Nepal and their employees. The study targeted the listed manufacturing companies in Nepal Stock Exchange and their employees as a sample. A sum of 570 respondents was approached using a random sampling technique, and 391 appropriately filled-up responses were recorded in the study. The survey instrument had two questions relating to the respondents' general information, 13 questions regarding CMATs, and five questions relating to the relevance of the study variables with organizational performance evaluation (OPE). The study uncovered a negative and significant association of CMATs with OPE in the NMCs. Researchers and professionals may utilize this study's outcome to upturn their insights, which encourages them to assist the NMCs in deploying modern and innovative management accounting techniques and practices.